A novel dual-function bithiophene-Meldrum's acid based chemosensor for highly sensitive, colorimetric and fluorimetric detection of cyanide and hypochlorite and its applications. (September 2020) - Li, Chunpeng; Niu, Qingfen; Li, Tianduo; Wei, Tao; Hu, Tingting; Chen, Jianbin; Qin, Xuyang; Yang, Lan
Abstract: A dual-function bithiophene-Meldrum's acid based chemosensor 2TM was developed, which displayed ultrafast, colorimetric and fluorescence turn-on responses for CN − and ClO − with specific selectivity and high sensitivity. The sensor 2TM for CN − detection in DMSO/H2 O (1/3, V/V) solution was based on the nucleophilic addition of CN − to sensor, which resulted in remarkable spectral and discernible color changes. Meanwhile, 2TM showed specific selectivity for ClO − in 100% aqueous solution based on the sensing mechanism of oxidative cleavage of CC bond. The detection limits were obtained to be 0.96 μM for CN − and 48 nM for ClO − . The sensing mechanism of 2TM toward CN − and ClO − was investigated by job'plot, FTIR, 1 H NMR, HRMS and optical spectra. The sensor 2TM loaded colorimetric test strips/supported silica measurements demonstrated to be a portable, eco-friendly and ultrafast device for real-time and on-site visual detection of CN − and ClO − in water by the naked eye. More importantly, sensor 2TM with excellent photophysical properties and low biotoxicity was successfully applied to detect CN − and ClO − in live cells and environmental water samples, as well as capable of monitoring CN − in the natural food samples, illustrating its practical utility in biological and environmental systems. Graphical abstract: Image 1 Highlights: A novel colorimetric and fluorescent sensor 2TM was introduced for simultaneous detection of CN − and ClO − . 2TM exhibits excellent selectivity, great sensitivity and ultrafast responses to CN − and ClO − . The low detection limits for CN − and ClO − were obtained as 0.96 μM and 48 nM. 2TM sensitively detect CN − and ClO − in live cells, water and food samples. 2TM is applied as an efficient sensor for highly colorimetric detection of CN − and ClO − on test strips and silica.